THE INTERPRETATION OF THE TOWN IMAGE IN THE UKRAINIAN LITERATURE OF THE 20-30TH YEARS OF THE XX CENTURY - Petrenko, L. YA. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article deals with the interpretation of the town image in the aspect of artistic principles of expressionism. On the material of creative work by Y. Pluzhnyk, M. Bazhan, T. Osmachka and other writers of the 20-40th years of the XX century it is analysed the phenomenon of a town inhabitant, a man of crowd, lonely and sensitive; a town contrasted to a village; the transition of a town into the apocalyptic plan.